POSSIBILITIES OF THERAPY OF HER-2-POSITIVE REGIONAL BREAST CANCER - A. S. Belokhvostova; Yu. А. Ragulin (Опухоли женской репродуктивной системы)
Breast cancer heads the list of malignant neoplasms in women. In this connection the regional forms of cancer are diagnosed in one fourth of the patients. The treatment of regional cancer begins with systemic therapy and aimed at gaining of state fit for operation. The choice of modern treatment strategy is based on determination of molecular subtype of the tumor. One of them is referred to HER-2-positive cancer, requiring the administration of additional targeted therapy. This form of cancer is referred to prognostically pejorative tumors, as it’s more aggressive, leads to fast metastasis and early death of the patients. The “golden standard” of systemic chemotherapy is defined as administration of docetaxel and trastuzumab,  and antracyclic drugs, which also prove to be efficient. However concomitant administration of trastuzumab and antracyclines is limited due to their cardiotoxicity. Chemotherapy is not always efficient and, upon recommendations both of Russian and international oncologists, radiotherapy is the next stage of treatment. The question about radiosensibility of HER-2-positive tumors is still open and worth studying. Addition of radiotherapy to regional cancer treatment regimen in combination with the targeted therapy and chemotherapy may contribute to obtaining better survival rate and disease control. There are still no clearly defined standard for the sequence of chemo-radiation therapy. Simultaneous  chemo-radiatiojn  therapy results in  reliably better loco-regional control of tumor and  enables to gain a  higher degree of pathomorphological response on the one hand, and it may result in development of serious adverse effects on the other hand. Striving for improvement of immediate results of antineoplastic therapy, including that of regional cancer, by combining various methods, one should keep in mind the increasing action toxicity, which may have a considerable impact on the patients’ quality of living. Continuation of experiments and clinical trials in this direction is rather actual, as it allows getting new data for treatment of regional breast cancer.